A phytoclimatic map of Europe - Dario Botti (Unité Mixte de Recherche 8504 Géographie-cités, 2018)
This paper presents a high-resolution quantitative phytoclimatic map of Europe (PME). Ecological studies and landscape planning need quantitative and reproducible tools to assess the environment and to define land based ecological units characterized by spatial and temporal boundaries. At small scales, Phytoclimatic maps seem appropriate to fulfill such requisites because climate determines broad ecosystem type and distribution. PME is based on Defaut’s system of phytoclimatic stages (DSPS). DSPS relies on a combination of mean annual temperature, mean temperature of the warmest month, thermal continentality and the Qn2 aridity/humidity index. Boundaries of phytoclimatic stages are defined by zonal phytosociological syntaxa. PME was developed by GIS processing, by kriging interpolation of phytoclimatic temperature classes, aridity/moisture and thermal continentality of 1113 climatological stations. PME shows fifty different phytoclimatic stages. Distribution and coverage of such stages and their main plant formations are described and discussed. PME was compared to the Map of the Natural Vegetation of Europe (MNVE) by Kappa analysis. Good agreement was found between PME and MNVE, but as expected, PME and MNVE do not match perfectly. Major circumstances that could lead to discordance between the two maps are discussed. In conclusion, it is felt that PME, thanks to its reliability and relative simplicity could be a useful and robust tool in ecological analysis and environment assessment, as well as in climate change studies, and for educational purposes.